Foreign owners and perceived job insecurity in Germany: Evidence from linked employer-employee data - Verena Dill; Uwe Jirjahn (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2014)
Using linked employer-employee data from Germany, we examine the role of foreign owners in employees' perceptions of job insecurity. Our estimates show that there tends to be a positive link between foreign owners and perceived job insecurity. The link is specifically strong for foreign-owned firms with high personnel turnover or poor employment growth. It is also stronger if the foreign-owned firm provides managerial profit sharing. However, the link is negative for foreign-owned firms with product innovations.
Keywords: F23; F66; J23; J28; J63; 330; foreign ownership; perceived job insecurity; managerial profit sharing; personnel turnover; product innovation